Respuesta :

Answer:

this

Step-by-step explanation:

Product Rule of Exponents aman = am + n

When multiplying exponential expressions that have the same base, add the exponents.

Example:

Multiply: 4x3 · −6x2

Solution:

Multiply coefficients: 4 · −6 = −24

Use the product rule to multiply variables : x3 · x2 = x3 + 2 = x5

4x3 · −6x2 = −24x5

Pat100

Answer:

this simply means that when multiplying indices the exponents must be added and the whole numbers will be multiplied in the normal way

ACCESS MORE